STRATEGI PENGARAH ACARA DALAM MENINGKATKAN KUALITAS PROGRAM JAMA’AH BERTANYA USTADZ MENJAWAB SEBAGAI SIARAN DAKWAH INTERAKTIF DI ASHIIL TV PEKANBARU - Jeffry Larsen; Tika Mutia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
In attracting audiences in da'wah media, Ashiil TV is a da'wah television centered in the city of Pekanbaru. The purpose of this study was to examine how the success of the behind-the-scenes program directing strategy in improving the quality of the Jama’ah Bertanya Ustadz Menjawab program on Ashiil TV Pekanbaru. This research uses the descriptive qualitative method. The research aims to describe descriptively the phenomena through the collection of interview and observation data. The results of this study contained four series of event steering strategies in improving the quality of the Jama’ah Bertanya Ustadz Menjawab programs, consisting of stages of planning, production, program execution, monitoring, and program evaluation. In its planning, the program includes ideas for making programs that come from suggestions and experiences, determining the format of the event in the form of interactive da'wah, targeting the target audience for all Muslim circles, facilities, and cost requirements for the Jama’ah Bertanya Ustadz Menjawab program. In the production process, it goes through the stages of standard operational produce (SOP) production, namely pre-production, production implementation which is led directly by the event director, and post-production. The Jama’ah Bertanya Ustadz Menjawab Program is executed with a broadcast pattern that is asked on an effective schedule and broadcast live on television via satellite and social media. The last stage is the supervision and evaluation carried out by the event director in post-production in the face of technical problems.